Fact Checking and Analyzing the Web - Goasdoue, Francois; Karanasos, Konstantinos; Katsis, Yannis; Leblay, Julien; Manolescu, Ioana; Zampetakis, Stamatis (International Conference on Management of Data (SIGMOD), 2013)
Fact checking and data journalism are currently strong trends. The sheer amount of data at hand makes it difficult even for trained professionals to spot biased, outdated or simply incorrect information. We propose to demonstrate FactMinder, a fact checking and analysis assistance application. SIGMOD attendees will be able to analyze documents using FactMinder and experience how background knowledge and open data repositories help build insightful overviews of current topics.